The Relationship of Islam and Locality in the Architecture of the Wapauwe Ancient Mosque in Maluku - Wuri Handoko; Isman Pratama Nasution; Wanny Raharjo Wahyudi; Herry Yogaswara; Muh. Subair; Nurman Kholis; Kadir Massoweang; Alfan Firmanto; Ali Akbar (Journal of Islamic Architecture, 2024)
The Wapauwe ancient mosque in Maluku is historically and culturally significant, symbolizing the enduring bond between religion and the local community. This qualitative archaeological study examines the mosque's architectural aspects to explore this connection. The mosque is considered a result of careful thought and reflects origin-related factors and human behavior through its architectural elements. The Wapauwe Mosque shares similarities with ancient mosques found throughout the archipelago. Its three-tiered roof typology, supported by four pillars and a distinctive peak, represents the three stages of Islamic development, showcasing the integration of Islamic principles with local culture. The two-tiered roof of the Wapauwe Kaitetu mosque signifies an ongoing dialogue between religious scholars and the indigenous people, leading to architectural adaptations. Furthermore, the mosque's design elements carry symbolic meanings. The peak symbolizes monotheism and male fertility, while the pineapple-shaped pegs embody the fusion of animal carvings and flora. The rectangular plan signifies the influence of customs and religion, and the mimbar type reinforces the growth and development of religious traditions. Architecturally, the Wapauwe mosque features 12 supporting pillars, corresponding to the 12 fundamental values of Islamic teachings—comprising the five pillars of Islam, six pillars of faith, and Ihsan. This alignment also mirrors the concept of deliberative custom, which includes 12 institutional structures. These structures coexist and interact with the religious hierarchy and its apparatus, demonstrating a balanced and inclusive relationship between religion and locality within the governance of Maluku. Ultimately, the typology of the Wapauwe mosque emphasizes the deep connection between Islam and local culture. It serves as a testament to the culturally inclusive religious character of the community. This cultural Islamic society respects differences and embraces diversity as an integral aspect of religious teachings